179k views
0 votes
Solve the following system of equations using the substitution method.–y = 5x + 21 –4x + y = 6

1 Answer

3 votes

The solution:

Given:


\begin{gathered} -y=5x+21...eqn(1) \\ -4x+y=6...eqn(2) \end{gathered}

Required:

To solve by the Substitution Method.

From eqn(1), we get:


y=-5x-21...eqn(3)

Putting eqn(3) into eqn(2), we get:


-4x+(-5x-21)=6

Clear the bracket:


\begin{gathered} -4x-5x-21=6 \\ \\ \text{ Collect the like terms:} \\ -9x=6+21 \\ \\ -9x=27 \end{gathered}

Divide both sides by -9.


x=(27)/(-9)=-3

Substitute -3 for x in eqn(3), we get:


y=-5(-3)-21=15-21=-6

Thus, the correct answer is (-3,-6)

User SenseException
by
5.0k points